Case report and systematic review of pulmonary embolism mimicking ST-elevation myocardial infarction. (February 2019) - Villablanca, Pedro A; Vlismas, Peter P; Aleksandrovich, Tatsiana; Omondi, Arthur; Gupta, Tanush; Briceno, David F; Garcia, Mario J; Wiley, Jose
Background: To study trends in the clinical presentation, electrocardiograms, and diagnostic imaging in patients with pulmonary embolism presenting as ST segment elevation. Methods: We performed a systematic literature search for all reported cases of pulmonary embolism mimicking ST-elevation myocardial infarction. Pre-specified data such as clinical presentation, electrocardiogram changes, transthoracic echocardiographic findings, cardiac biomarkers, diagnostic imaging, therapy, and outcomes were collected. Results: We identified a total of 34 case reports. There were 23 males. Mean age of the population was 56.5 ± 15.5 years. Patients presented with dyspnea (76.4%), chest pain (63.6%), and tachycardia (71.4%). All patients presented with ST-elevations, with the most common location being in the anterior-septal distribution, lead V3 (74%), V2 (71%), V1 (62%) and V4 (47%). ST-segment elevations in the inferior distribution were present in lead II (12%), III (18%), and aVF (21%). Presentation was least likely in the lateral distribution. Troponin was elevated in 78.9% of cases. Right ventricular strain was the most common echocardiographic finding. Over 80% of patients had findings consistent with elevated right ventricular pressure, with 50% reported RV dilatation and 20% RV hypokinesis. The most commonly used imaging modality was contrast-enhanced pulmonary angiography. There was a greater incidence of bilateral compared to unilateral pulmonary emboli (72.4% vs. 10%). About 65% patients received anticoagulation and 36.3% were treated with thrombolytics. Forty-six percent of patients required intensive care and 18.7% intubation. Overall mortality was 25.8%. Conclusions: A review of the literature reveals that in patients presenting with pulmonary embolism, electrocardiogram findings of ST-segment elevations will occur predominantly in the anterior-septal distribution.